2015
DOI: 10.1002/maco.201508410
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of Zn-Cu-Ti and Zn-Cu-Ti-Mg alloys in NaCl solution

Abstract: In the present investigation the microstructure and corrosion behavior of Zn‐Cu‐Ti and Zn‐Cu‐Ti‐Mg alloys in 3.5 wt% NaCl solution were studied through scanning electron microscope, electron probe microanalysis, X‐ray diffraction, polarization measurements and immersion tests. The Zn‐Cu‐Ti exhibited eutectic structure with rod‐shaped TiZn15 phase, while the Zn‐Cu‐Ti‐Mg mainly consisted of Zn matrix, TiZn15, τ2‐Cu2TiZn22 ternary phase and Zn‐Mg intermetallics along the grain boundaries. It was observed that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The phase and shape of corrosion products and corrosion layer thickness of the bare and treated alloys were characterized after 8 days of immersion in 3.5% NaCl solution, as shown in 3b, c). Wang and Ji reported similar results in corrosion experiment of Zn-Cu-Ti alloy [1,4]. It is measured that its thickness of corrosion layer is about 67μm (Figure 3d).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…The phase and shape of corrosion products and corrosion layer thickness of the bare and treated alloys were characterized after 8 days of immersion in 3.5% NaCl solution, as shown in 3b, c). Wang and Ji reported similar results in corrosion experiment of Zn-Cu-Ti alloy [1,4]. It is measured that its thickness of corrosion layer is about 67μm (Figure 3d).…”
Section: Resultssupporting
confidence: 54%
“…It is observed that Zn matrix overall grows in near‐equiaxed grain with dendritic characteristic (Figure 1b). Many small particles locate at grain boundaries and secondary dendrite gap (Figure 1c), which should be TiZn 3 phase based on the previous work [4]. After ZnOHF/ZIF‐8 composite grew on the surface of the Zn substrate, its surface becomes very coarse (Figure 1d, e).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations